Relación de conductas agresivas y rendimiento académico en estudiantes de segundo grado en una institución educativa del municipio de Hatonuevo
The objective of this research was to establish the relationship between aggressive behaviors and the academic performance of second grade students at the Inter-American Christian Educational Center of Hatonuevo, La Guajira. The central theme focused on how disruptive behaviors, such as aggression, negatively affect children's academic performance. The theoretical approach was based on previous research regarding the influence of aggressive behaviors on academic performance, as indicated by Fuentes (2017) and Díaz & Hernández (2019), who argue that aggression interferes with students' ability to concentrate and collaborate, key aspects of the learning process. The methodological design was quantitative, descriptive, and correlational, using a field design.